Pengaruh Problem Based Learning dengan Pendekatan Jelajah Alam Sekitar (JAS) terhadap Motivasi dan Hasil Belajar Kognitif Peserta Didik pada Materi Perubahan Lingkungan : (The Influence of PBL with the Environmental Exploration Approach (JAS) on Students Motivation and Cognitive Learning Outcomes on Environmental Change Material) - Tsalatsatunnisa', Ghina; Prajoko, Setiyo; Alamsyah , Muhammad Radian Nur (BIODIK, 2025)
This study was motivated by the suboptimal biology learning process at SMA N 5 Purworejo, which was caused by the low learning motivation and cognitive outcomes of students. One of the factors causing this is the use of the Teacher Centered Learning (TCL) model, which makes students feel bored and uninterested. Based on interviews with teachers in October 2023, it was found that only 30% of students reached the Criteria for Implementation of Learning Objectives (KKTP), while the rest had not met these criteria. This study aims to determine the effect of the Problem Based Learning (PBL) model with the Explore Nature Around (JAS) approach on motivation and cognitive learning outcomes of students on environmental change material. The method used is quasi experiment with Non-equivalent Control Group Design, with class X6 as control and X7 as experiment. Sampling was done by purposive sampling, and data analysis using ANCOVA test. The results showed that the PBL model with the JAS approach had a significant effect on motivation (significance value 0.006) and cognitive learning outcomes (significance value 0.000). Thus, it can be concluded that the application of the PBL model with the JAS approach is effective in increasing the motivation and cognitive learning outcomes of students on environmental change material. Key words: PBL, Motivation, Cognitive, JAS, Environmental Change